The Pelvis and Beyond: Musculoskeletal Tender Points in Women With Chronic Pelvic Pain. Issue 8 (August 2016) - Sanses, Tatiana V. D.; Chelimsky, Gisela; McCabe, Noel P.; Zolnoun, Denniz; Janata, Jeffrey; Elston, Robert; Buffington, C.A. Tony; Simpson, Pippa; Zhang, Liyun; Chelimsky, Thomas
Abstract : Objective: To determine the feasibility of a detailed pain sensitivity assessment using body-wide musculoskeletal tender points (TPs) in women with different types of chronic pelvic pain (CPP) and compare phenotypic differences. Materials and Methods: Seventy women with CPP and 35 pain-free women underwent musculoskeletal evaluation of TPs in the pelvic floor, abdomen, groin, inner thigh, and all 18 fibromyalgia TPs. Patients scored elicited pain on a numeric rating scale. TP pain scores were used for intergroup comparison and intragroup correlation. Results: Women with CPP were grouped as having either bladder pain syndrome (BPS, n=24) or myofascial pelvic pain (MPP, n=11) singularly or both concomitantly (BPS+MPP, n=35). TP pain scores for all evaluations were higher in women with CPP compared with healthy women ( P <0.001). Women with BPS+MPP had elevated TP pain for each evaluation compared with women with BPS alone. Pelvic floor and fibromyalgia TP scores correlated strongly in the MPP group, moderately in the BPS+MPP group, and weakly in the BPS alone group. Although some moderate and strong correlations between different body locations were present in all 3 groups, only the BPS+MPP group showed moderate to strong correlations between all body TPs. Conclusions: Detailed musculoskeletal evaluation of women with CPP is feasible and well tolerated. Careful phenotyping differentiated BPS, MPP, and BPS+MPP groups. Attending to the differences between these groups clinically may lead to more effective treatment strategies and improved outcomes for patients with CPP.